PATHOGENETIC MECHANISMS OF DYSLIPIDEMIA IN PUBERTY IN GIRLS: THE CONTRIBUTION OF HORMONAL RECONSTRUCTION TO THE INCREASE IN ATHEROGENICITY - Salomova Shakhinabonu Olimovna (Modern American Journals, 2025)
The article examines the pathogenetic mechanisms of lipid spectrum disorders in girls during puberty . The role of hormonal changes, insulin resistance , obesity and inflammatory processes in the formation of the atherogenic profile and metabolic syndrome is highlighted. Particular attention is paid to clinical studies of recent years demonstrating the relationship between changes in lipid metabolism and increased cardiometabolic risks in adolescents.
Keywords: puberty, adolescent girls, lipid spectrum, dyslipidemia, atherogenicity, metabolic syndrome, insulin resistance